Fourteen-year status report of fatal illnesses in captive chinchilla (Chinchilla lanigera) - Martino, Pablo Eduardo (2017)
Fur ranching has been a prosperous industry for decades. Despite its worldwide distribution, little published information is available regarding the importance of the various causes of death in chinchilla (Chinchilla lanigera). In the period 1999–2013, 698 captive chinchillas from different commercial ranches were presented for necropsy at the Pathology Department (UNLP). Two-hundred and forty-four animals (35.0%) had classical enteritis, 198 (28.4%) had pneumonia, 63 (9.0%) had other infections, 40 (5.7%) had traumatic injuries, 109 (15.6%) had miscellaneous conditions, meanwhile 44 (6.3%) had no significant lesions. Although some disease processes may be underrepresented (i.e. heat stroke and the shock syndrome), the data were collected from a field wide enough and over a sufficient period to give a reliable overview of the fatal problems of this rodent in captivity.